Printed, wearable e-skin force sensor array. (January 2023) - Sapra, Samta; Chakraborthy, Aniket; Nuthalapati, Suresh; Nag, Anindya; Inglis, David W.; Mukhopadhyay, Subhas Chandra; Ercan Altinsoy, Mehmet
Graphical abstract: Highlights: Fabrication of printed, wearable and flexible sensors has been done. The sensor patches were considered as electronic skins in capacitive force sensing applications. The operating of the sensors was carried out in shunt mode of the capacitive molding process. The testing was done using the electrochemical impedance spectroscopy technique. The sensors achieved a resolution of 2.5 sq. mm, localization accuracy of 99% and a sensitivity of 0.53 pF/N. Abstract: The need to develop electronic skin (e-skin) for robotics is essential to provide a sense of touch on a large area, the same as human skin. This paper reports the design and development of printed e-skin force sensor arrays. The performance analysis of these capacitive force sensor arrays showed a resolution of 2.5 sq. mm, localization accuracy of 99% and a sensitivity of 0.53 pF/N. The sensor patches provided significant force sensitivity and stable loading and unloading for static force. A graphical user interface is developed in open-source python software. An unsupervised machine learning algorithm trains the tactile e-skin system for different user styles to distinguish the cluster of lower and higher touch angles for improving accuracy. The proposed e-skin sensor finds application in large-area sensors and gripper pads for prosthetics in biomedical devices where the sense of touch and high resolution is needed.